Transparency and Bank Liability Structure - Jiang, Xu; Mahieux, Lucas (The Accounting Review, 2026)
ABSTRACT We study the desirability of transparent accounting information for banks depending on their liability structure. In our model, a bank finances a long-term project with both uninsured and insured deposits. Although uninsured deposits increase rollover risk, they may also generate efficient liquidations. Importantly, a transparent regime provides timelier information about the project’s payoff than an opaque regime. We show that the transparent regime is surplus-enhancing when the amount of insured deposits is small, as the bank issues the optimal amount of uninsured deposits and transparency leads to efficient liquidations. Otherwise, when the amount of insured deposits is large, the cost of inefficient liquidations dominates, making the opaque regime optimal. In addition, the bank may favor transparency to reduce its funding cost even when it is surplus-decreasing. Overall, our results show that transparent accounting is not a panacea and provide some support for the “mark-to-funding” accounting rule. JEL Classifications: G20; G28; M41; M48